The environmental risk factors associated with fetal macrosomia: An umbrella review - Ensiyeh Jenabi; Amir Mohammad Salehi; Sajjad Farashi; Zohreh Salimi (Pediatrics and Neonatology)
The present umbrella review evaluated the environmental risk factors prior to conception associated with fetal macrosomia based on meta-analyses and systematic reviews. We systematically searched international databases, including PubMed, Scopus, and Web of Science, until April 2023 by using some relevant keywords. The quality of the included studies was assessed using the AMSTAR 2checklist. The risk factor of advanced maternal age 35–39 years compared with <30 years (OR 1·42, 95 % CI: 1·25, 1·60), prepregnancy obesity (OR 1.93, 95 % CI: 1.65, 2.27) and excessive weight gain before and during pregnancy (OR 2.35, 95 % CI: 1.95, 2.85) were graded as suggestive evidence (class III). Two risk factors of advanced maternal age >40 years compared with <30 years (OR 1.40, 95 % CI: 1.02, 1.78) and gestational diabetes mellitus (GDM) without insulin use (OR 1.70, 95 % CI: 1.23, 2.36) were graded as risk factors with weak evidence (class IV). Advanced maternal age, prepregnancy obesity, excessive weight gain before and during pregnancy, and GDM without insulin use were environmental risk factors for macrosomia.